PENYELESAIAN SENGKETA PERBANKAN SYARIAH (Kritik atas Contradictio in Terminis Pasal 55 Undang-undang no. 21 Tahun 2008 Tentang Perbankan Syariah) - Thalis Noor Cahyadi (Universitas Alma Ata, 2011)
The developing of Islamic banking is an interesting phenomenon in the world society, especially in the Moslem countries. Indonesia as the biggest Moslem country has magnitude potential to develop and innovate in the integrated system especially through creating regulations and laws. However, in the process lot of problems arise, particularly in the matter of dispute resolve. The law of religious court states that the dispute of Islamic banking under its authority. But the law of sharia banking states that there is option to solve the dispute. It can be through the religious court or through the general court. It depends on the will of the parties. This article will explore about contradiction in terminis in the law of sharia banking.Keyword: sengketa, kewenangan, regulasi, penyelesaian, pertentangan, kontradiksi